Impact of obesity in favorable‐risk AML patients receiving intensive chemotherapy. Issue 2 (26th November 2015) - Tavitian, Suzanne; Denis, Amélia; Vergez, François; Berard, Emilie; Sarry, Audrey; Huynh, Anne; Delabesse, Eric; Luquet, Isabelle; Huguet, Françoise; Récher, Christian; Bertoli, Sarah
Abstract : We assessed the influence of obesity on the characteristics and prognosis of acute myeloid leukemia (AML). Indeed, safety of intensive chemotherapy and outcome of obese AML patients in a real‐life setting are poorly described, and chemotherapy dosing remains challenging. We included 619 consecutive genetically‐defined cases of AML treated with intensive chemotherapy between 2004 and 2012. In this cohort, 93 patients (15%) were classified in the obese category according to WHO classification; 59% of them received capped doses of chemotherapy because of a body surface area above 2 m 2 . Obese patients were older and presented more often with cardiovascular comorbidities. Although obese patients had more frequently de novo AML, main characteristics of AML including white blood cell count, karyotype and mutations were well‐balanced between obese and non‐obese patients. After induction chemotherapy, early death and complete remission rates were similar. Overall (OS), event‐free (EFS) and disease‐free (DFS) survival were not significantly different compared to non‐obese patients. However, in the European LeukemiaNet (ELN) favorable subgroup, obese patients had lower median OS, EFS and DFS than non‐obese patients (18.4, 16.8 and 17.2 vs. 43.6, 31.8 and 29.7 months, respectively) and obesity showed a significant impact on OS (OR 2.54; P  = 0.02) in multivariate models. Although we did not find any significant impact of obesity on outcome in the whole series, this study suggests that special efforts for chemotherapy dose optimization are needed in the ELN favorable subgroup since dose capping may be deleterious. Am. J. Hematol. 91:193–198, 2016. © 2015 Wiley Periodicals, Inc.